How to easily detect plant NADH-glutamate dehydrogenase (GDH) activity? A simple and reliable in planta procedure suitable for tissues, extracts and heterologous microbial systems - Marchi, L (Plant science : an international journal of experimental plant biology, 2021)
Copyright © 2020 Elsevier B.V. All rights reserved.